Factors contributing to emotional distress when caring for children with imperforate anus: a multisite cross-sectional study in China - Lv, Meng; Feng-Fang, Ya; Wang, Yi; Zhen-Xu, Hong (Frontiers in Medicine, 2023)
Background Imperforate anus (IA) has a life-long impact on patients and their families. The caregivers of children with IA (CoCIA) might experience distress, which could be detrimental to them physically and mentally. However, there are limitations in the related studies. This study aimed to investigate the prevalence of IA and the associated factors contributing to the distress experienced by CoCIA. Methods A cross-sectional study was conducted in three tertiary children's hospitals from November 2018 to February 2019. Distress was assessed using the Chinese version of the Kessler Psychological Distress Scale, and possible determinants were assessed by the Caregiver Reaction Assessment, the Parent Stigma Scale, the Parent Perception of Uncertainty Scale, and the Social Support Scale. Demographic and clinical information was also collected. Multiple regression analysis was performed to explore the association between variables. Results Out of 229 CoCIA, 52.9% reported experiencing a high level of distress or above. The data analysis revealed that health problems associated with caregiving, stigma, uncertainty, social support, and children who underwent anal reconstruction surgery 1 year before or earlier could significantly predicate caregivers' distress, and these factors could explain 50.1% of the variance. Conclusions The majority of the caregivers of children with IA experience high levels of distress, particularly when their children undergo anal reconstruction surgery 1 year before or earlier. Additionally, health problems related to caregiving, stigma, uncertainty, and low social support could significantly predicate caregivers' distress. It is important for clinical staff to be aware of the prevalent situation of caregivers' distress and to make targeted interventions focused on addressing modifiable factors that should be carried out in family-based care.